Unraveling the Complexities of Social Capital: A Comprehensive Review - Bhandari, Pawan Singh (Nepalese Journal of Development and Rural Studies, 2024)
Social capital plays a crucial role in development. It facilitates cooperation among individuals and groups. This is particularly significant in rural areas of developing countries where access to productive capital is limited, thereby impeding the improvement of livelihoods. However, it is crucial to acknowledge that social capital can have both favorable and unfavorable effects. Studying social capital is therefore imperative in order to develop a conceptual understanding and harness its positive benefits. This paper presents a comprehensive review of the literature on social capital. It systematically summarizes and organizes relevant information from various publications to achieve a comprehensive understanding of this complex concept. Social capital encompasses multiple dimensions, forms, and levels. It is increasingly recognized as a valuable asset for development. Nonetheless, its effectiveness in promoting development is subject to debate due to issues such as unequal access and potential adverse outcomes. A thorough understanding of social capital is indispensable to devising effective policies and guiding development interventions. This understanding will help in determining the most effective forms and dimensions of social capital, while mitigating its negative repercussions.